Improving nutrient removal performance of surface flow constructed wetlands in winter using hardy submerged plant-benthic fauna systems. Issue 73 (18th December 2018) - Guo, Ying; Xie, Huijun; Zhang, Jian; Wang, Wengang; Ngo, Huu Hao; Guo, Wenshan; Kang, Yan; Zhang, Bowei
Abstract : A novel hardy submerged plant-benthic fauna systems to enhance the performance of surface flow constructed wetlands in winter. Abstract : Constructed wetlands (CWs) have been widely used as an ecological technology for removing nutrients from aquatic ecosystems. However, the treatment efficiency of surface flow constructed wetlands (SFCWs) in winter is generally low. To enhance the nutrient removal performance of SFCWs in winter, we developed a novel hardy submerged plant-benthic fauna system by adding Chironomus riparius ( C. riparius ) larvae and planting Potamogeton crispus L. in SFCWs. Compared to a system without C. riparius, the paired system greatly enhanced TN and TP removal with the average removal efficiencies of 54.73% and 94.76%, respectively. Furthermore, the paired system improved NO3 − –N removal efficiency by 29.51% and reached NH4 + –N removal efficiency as high as 86.20% simultaneously. The mass balance analysis indicated that C. riparius larvae enhanced substrate absorption and plant uptake in the CWs. The results of microbial analysis agreed with the nutrient removal performance, showing that C. riparius larvae influence the abundance and community structure of microbes related to N removal. As a whole, this study provides a promising ecological strategy for performance intensification of SFCWs in winter.